Design A Model of A Windfield With 12 Inch Blade Sizes - Giovane Nafico; Estu Prayogi; Hary Soebagyo (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The design of this windmill model is made to be able to design how effective the windmill is in producing rpm and power values, especially 12 inch blades. The design method carried out is the planning method and continued with experimental testing. While the design method used is the design with the Pahl & Beitz method, starting from planning and task explanation, product concept planning, shape design and detail design. Supported through several supporting applications, namely solid works, ansys, and AutoCAD, as well as analysis of calculations carried out through formulas obtained in several references through the resulting numbers we can find the absolute value of speed, power and rpm and blades of windmill blades. The calculation analysis obtained becomes a reference in making the blade to get the most effective blade in order to produce the maximum appropriate value. This research uses 12 inch blades and a blower with a maximum power of 300 rpm. The turbine design results obtained through ansys simulation have the highest value of 13.6 m / s on the vertical shaft windmill and 52.2 m / s on the horizontal shaft windmill. While in the calculations obtained through windmill design experiments, the amount of windmill rpm obtained depends on the amount of rpm generated by the blower. The greater the rpm generated by the blower, the greater the windmill rpm value. Similarly, the value of windmill speed is the greater the rpm generated by the windmill, the greater the value of the windmill speed. The blower used is a blower that produces the highest rpm of 2900 rpm. Then the highest resulting wind is 5.03 m/s. In addition to the above calculations, testing was also carried out using the application, namely Ansys, where the maximum effective value was obtained to be able to produce windmills. The maximum speed value obtained through the ansys application is 42.55 km/s.Â